PARENTING STYLE AND LEARNING INDEPENDENCE AS DETERMINANTS OF STUDENT ACADEMIC ACHIEVEMENT: - Syafitri, Deswita; Faslah, Roni; Wolor, Christian Wiradendi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
The student learning process at school is influenced by internal and external factors, including the role of parents and the students' ability to learn independently. This study aims to examine the influence of Parenting Patterns and Learning Independence on Learning Outcomes. The research methodology used in this study is quantitative. The data used are primary data through questionnaires, and secondary data obtained from schools. Data analysis for hypothesis testing uses Multiple Linear Regression with the help of SPSS Version 30.00 software. The results show that Parenting Patterns and Learning Independence have a positive effect on Learning Outcomes both partially and simultaneously. This finding confirms that parental support in forming appropriate parenting patterns and developing learning independence is an important factor in improving student achievement at the vocational high school level.